Borrowing constraints, the cost of precautionary saving and unemployment insurance - Thomas F. Crossley; Hamish Low (Institute for Fiscal Studies (IFS), 2005)
Job losers exhibit significant heterogeneity in wealth holdings and in the marginal propensity to consume transitory income. We consider potential sources of this heterogeneity, whether (some of) the unemployed face borrowing constraints, and the implications of this heterogeneity for unemployment insurance. We show theoretically how the optimal benefit can depend significantly on borrowing constraints, and on other (nonprecautionary) savings motives. We report empirical evidence that (i) a quarter of job losers cannot borrow for current consumption, (ii) this constraint is binding for a much smaller fraction, and (iii) that éxcess sensitivityís not limited to the constrained.
Keywords: 330; Arbeitslosigkeit; Verschuldungsrestriktion; Haushaltseinkommen; Sparen; Lebenszyklus; Kanada